(untitled) (Academic Journal of International University of Erbil, 2025)
This study aims to determine the effect of organizational Integrity, represented by the dimensions of (Optimism, Trust, Empathy, and Tolerance) on organizational Symmetry, represented by (Loyalty, Similarity, and Membership) in the public and private sectors in the KRI. Researchers used probability sampling to collect the data via a Google form (n = 144) using SPSS software V.26. Data were analyzed using descriptive statistics to find the frequencies and percentages of the demographic questions. The Chi-Square Test was used to find the association relationship between variables; researchers used Spearman’s rank-order correlation and regression analysis to show the correlation and the impact of organizational Integrity on organizational Symmetry. Results show no statistical relationship between demographic variables and respondents' opinions about how Integrity affected organizational Symmetry. A positive and significant correlation exists between organizational integrity and organizational Symmetry. In addition, results show that there is a statistically significant effect of organizational Integrity (Empathy and Tolerance) on organizational Symmetry (Loyalty and Similarity) and there is a statistically significant effect of one of the dimensions of organizational Integrity (Tolerance) on one of the dimensions of organizational Symmetry (Membership).